2018
DOI: 10.1177/1747493018806165
|View full text |Cite
|
Sign up to set email alerts
|

Weekend hospital discharge is associated with suboptimal care and outcomes: An observational Australian Stroke Clinical Registry study

Abstract: Background: The quality of stroke care may diminish on weekends. Aims: We aimed to compare the quality of care and outcomes for patients with stroke/transient ischemic attack discharged on weekdays compared with those discharged on weekends. Methods: Data from the Australian Stroke Clinical Registry from January 2010 to December 2015 (n ¼ 45 hospitals) were analyzed. Differences in processes of care by the timing of discharge are described. Multilevel regression and survival analyses (up to 180 days postevent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Concerns have been raised that the quality of in-patient care that people receive may vary according to the day of the week. 1 Clinical outcomes may be worse among patients who are admitted to 2–7 and discharged from 8 acute hospitals at the weekend compared with those admitted and discharged during the ‘working week’.…”
mentioning
confidence: 99%
“…Concerns have been raised that the quality of in-patient care that people receive may vary according to the day of the week. 1 Clinical outcomes may be worse among patients who are admitted to 2–7 and discharged from 8 acute hospitals at the weekend compared with those admitted and discharged during the ‘working week’.…”
mentioning
confidence: 99%
“…Patients who are discharged on a weekend less often receive a care plan at the time of hospital discharge than those discharged during the week, as do those discharged to an aged care facility [ 19 ]. Discharge processes for patients with stroke may be particularly sensitive to resourcing deficits on weekends, as care planning requires interactions between a diverse range of healthcare professionals from the multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the factors influencing the receipt of discharge care plans in the acute stroke care setting is necessary to guide improvements to this aspect of recommended care. Prior research on factors associated with discharge care planning after acute stroke has been limited to the investigation of single or few factors [ 16 , 17 , 18 , 19 , 20 , 21 ]. We aimed to comprehensively evaluate patient, clinical and system factors associated with receiving a discharge care plan after acute stroke/TIA in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Bell et al reported that patients admitted on weekends with ruptured abdominal aortic aneurysms, acute epiglottitis, and pulmonary embolism are associated with higher in-hospital mortality rates than those who were admitted on weekdays for the same problems [7]. An Australian study done among stroke/transient ischemic attack patients reported that patients discharged on weekends received suboptimal care and had higher long-term mortality compared to those discharged on weekdays [8].…”
Section: Introductionmentioning
confidence: 99%